Counter-Narrative of Radical Religious Beliefs of Jihadist Groups: A Study of the Kutb Sittah Hadith Books on Tolerance - Auzan, Ahmad Isyraq Jamarul; Ash, Abil; Muzakki, Muhammad Asgar; Sahid, Mualimin Mochammad (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
Understanding of tolerance in Islam often varies and becomes a subject of different interpretations. This can create the potential for misunderstanding or misuse of tolerance in everyday practice. The purpose of this article is to analyze the understanding of jihadist groups regarding the relevant hadiths in Kutb Sittah that pertain to the concept of tolerance. This article is qualitative, utilizing content analysis to collect, analyze, and interpret textual data related to the research topic, in this case, the concept of tolerance in hadiths. This article asserts that jihadist groups that adopt radical religious beliefs do not reflect the values of tolerance. In contrast, the hadiths in Kutb Sittah emphasize the principles of tolerance in Islam, including ease, non-compulsion in religious beliefs, and the importance of maintaining good relations with fellow human beings. Therefore, these counter-narratives are relevant in combating radical interpretations that do not align with the values of tolerance, as well as social theories of tolerance that strengthen the importance of understanding and applying the concept of tolerance in an increasingly complex and multicultural society. With a deeper understanding of the true meaning of tolerance in Islam, it is hoped that there will be a stronger foundation for promoting harmony among religious communities, respecting diversity, and avoiding religious conflicts. Pemahaman tentang toleransi dalam Islam seringkali dapat bervariasi dan menjadi subjek interpretasi yang berbeda. Hal ini dapat menciptakan potensi untuk pemahaman yang salah atau penyalahgunaan konsep toleransi dalam praktik sehari-hari. Tujuan artikel ini untuk menganalisis pemahaman kelompok jihadis terhadap hadis-hadis dalam Kutb Sittah yang relevan dengan konsep toleransi. Artikel ini bersifat kualitatif dengan menggunakan content analysis, yang bertujuan untuk mengumpulkan, menganalisis, dan menginterpretasi data teks yang berkaitan dengan topik artikel, dalam hal ini, konsep toleransi dalam hadis. Artikel ini menegaskan bahwa kelompok jihadis yang mengadopsi paham keagamaan radikal tidak mencerminkan nilai-nilai toleransi, sementara hadis-hadis dalam Kutb Sittah menekankan prinsip-prinsip toleransi dalam Islam, yang mencakup kemudahan, ketidakpaksaaan keyakinan agama, dan pentingnya menjaga hubungan baik dengan sesama manusia, sehingga kontra-narasi ini relevan dalam memerangi pemahaman radikal yang tidak sesuai dengan nilai-nilai toleransi, serta teori toleransi dalam ilmu sosial yang memperkuat pentingnya memahami dan menerapkan konsep toleransi dalam konteks masyarakat yang semakin kompleks dan multikultural. Dengan pemahaman yang lebih mendalam tentang makna sebenarnya dari toleransi dalam Islam, diharapkan dapat menjadi landasan yang lebih kuat untuk mempromosikan kerukunan antarumat beragama, menghormati keberagaman, dan menghindari konflik agama.